Penerapan Pendekatan Pembelajaran CRT (Culturally Responsive Teaching) untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila di Kelas V SDN 6 Cakranegara Tahun Ajaran 2024/2025 - Sari, Dewi Anitia; Tahir, M.; Herawati, Sri (Mataram University, 2025)
This study aims to improve the learning outcomes of fifth-grade students in the subject of Pancasila Education through the implementation of the Culturally Responsive Teaching (CRT) approach. The research employed a Classroom Action Research (CAR) design conducted in two cycles, focusing on enhancing students’ academic achievement during the learning process. The participants of this study were 25 students from SDN 6 Cakranegara. Data were collected through tests and observation sheets using a purposive sampling technique, and analyzed using both quantitative and qualitative methods.The findings revealed that, during the pre-cycle stage, the students’ classical mastery level was 28%, with 7 students achieving mastery and 18 students not yet meeting the criteria. After the implementation of the CRT learning model in Cycle I, the mastery level increased to 60%, with 15 students achieving mastery and 10 students remaining below the standard. In Cycle II, the mastery level further increased to 88%, with 22 students achieving mastery and only 3 students not yet achieving mastery. These results indicate that the implementation of the Culturally Responsive Teaching model is effective in improving students’ learning outcomes on the topic of cultural diversity within the context of unity and integrity in the Indonesian nation.